An Analysis of Students’ Challenges in Interactive English Speaking Through Group Discussions - Yanani Syafitri; Feby Meuthia Yusuf; Widya Juli Astria (Kilau Publishing, 2024)
Speaking is a communicative and repetitive activity supported by simple structure and clear meaning. This study aimed to identify speaking difficulties among second-semester students of the English Department at FKIP Universitas Ekasakti. The main problems found were lack of pronunciation, grammar, and vocabulary. The research used a descriptive quantitative method. The population consisted of 11 students, and total sampling was applied, meaning all students participated. A speaking test was used as the research instrument. Students were asked to perform in front of the class, and their speaking abilities were analyzed using specific speaking indicators.The results showed that out of 11 students, 1 student achieved a very good level, 8 students were in the good category, and 2 students were in the average category. The overall average score was 76, indicating that students’ speaking ability, especially in interactive speaking through group discussion, was at a good level.